The Potency of Jarak Pagar (Jatropha curcas Linn) as a Fuel Break Based on Canopy Condition - Lailan Syaufina; Nurheni Wijayanto; Istomo Istomo; Yuli Sunarti (Jurnal Silvikultur Tropika, 2011)
It is assumed that Jarak pagar (Jatropha curcas Linn) has potency for fuel break in forest fire control.  However, it needs to be evaluated in effectiveness of the function.  One of the requirement as fuel break is crown condition in which the plant crown need to have good performance in covering the area to prevent fire sppread. A study was conducted to analyze whether Jarak pagar meets the requirement for fuel break or not.  Some sample plots were established in forest plantation area of Gunung Hambalang, Bogor managed by Perhutani.  The study resulted that Jarak pagar in the study area does not meet the requirement for fuel break of which a good performance of crown is not shown.  It seems that soil characteristics influenced the result.